DESIGN OF MODERN PEDAGOGICAL TECHNOLOGIES AND INTERACTIVE METHODS IN TEACHING HISTORY (Scientific journal of the Fergana State University, 2023)
It is known that the main purpose of education is not only to educate students, but also to teach them how to learn, to make them active participants in the educational process. Improving the system of education in the new social and economic conditions, the organization of lessons in accordance with international standards are important factors in increasing student activity.This article examines the design of modern pedagogical technologies and interactive methods in the teaching of history.